Tra cứu hàm Excel - Nguyễn Duy Hòang Mỹ (Nhà xuất bản Giao thông Vận tải, 2005)
Chương I: Hàm quản lý cơ sở dữ liệu và danh sách: Daverage, Dcounta, Dget, Dmax, Dmin, Dprouct, Dstdev, Dstdevp, Dsum, Dvar, Dvarp, Getpivotdata.